The Horizon of an African Philosophical Hermeneutics - (:unkn) unknown (My University, 2025)
This article aims to highlight the broad conception of interpretation that African hermeneutics proposes in its emancipation from the Western scriptural textual model. Indeed, since contemporary African hermeneutics establishes itself as a gnoseology of African philosophical singularity, rather than fully adopting the written paradigm of hermeneutics, it is essential to clarify how the thought of understanding and interpreting the being of African singularities follows a completely different hermeneutic approach. In fact, African philosophical hermeneutics is shaped by the uniqueness of African modes of transmission. Thus, the transition from oral tradition to written tradition, which is now established, cannot disregard what defines the specificity of African philosophical hermeneutics. Its theoretical appropriation has been a consequence of the challenges imposed by the imperialism of scriptural hermeneutic theories, which often exclude oral traditions. Furthermore, a non-restrictive conception of the notion of text or literature – one that extends beyond scripturality to encompass an oral tradition deeply embedded within cultural heritage – allows us to reconsider the limitations of contemporary hermeneutics. It also underscores the necessity of a more inclusive hermeneutic transformation. This suggests that hermeneutic theory should not be static but can evolve through encounters with new experiences and traditions.
Keywords: African Research